Художня література, кіно і пісні в інтертексті роману С. Оксеника "Вбивство п’яної піонерки": кодифікація ретрочасу - Даниленко, Людмила Вікторівна; Danylenko, L. (Київ: НаУКМА, 2018)
У статті розглянуто інтертекстуальне тло в романі Сергія Оксеника "Вбивство п ’яної піо- нерки". Ідеться про використання художньої літератури, кіно і пісень як джерела зображення ретрочасу. Виявлено, що система мікротекстів в основному тексті відображає атмосферу 1960-х років. Проаналізовано цитати, алюзії, стилізацію як прийоми для художнього конструювання суспільних і моральних проблем того часу. Визначено, що цитування чужих текстів у романі забезпечує своєрідну поліфонічність основного тексту, увиразнює часовий пласт мистецьких пріоритетів і рівня культури персонажів. Використовуючи чужі тексти, автор розраховував на ерудицію і мистецькі уподобання читача, зробив натяки на характери відомих героїв літератури, кіно та естради. Вказано на те, що завдяки інтертексту у площині постпам’яті активізовано промовисті деталі, відчуття та емоції, які розвінчують радянський міф і пояснюють проблеми сучасного українського суспільства. The article is devoted to the specific of the visualization of the Soviet retro-time in the novel by Serhii Oksenyk "The Murder of Drunk Pioneer" (2018). It is noticed that modern Ukrainian writers rethink the memory of life in the Soviet Union more and more often. Many of them were the contemporaries of the Soviet era. They represent their personal memories and feelings, stylize the past, reflecting the paradoxes of that epoch and combining satirical-revealing and sensual-intimate aspects. The article considers the intertextual background in the novel of Serhii Oksenyk «The Murder of Drunk Pioneer». The main text reveals a system of microtexts, taken from the books of Ukrainian and foreign authors, which were available in the Soviet period, and quotes from cinema and songs popular in the 1960s. The article analyzes the quotation, quotes, allusions, stylization as reception of the social and moral problems of the past time. It is indicated that real life and atmosphere ofpeople’s interests in the plot of the novel is dynamic and sensual. In the intertextual projection, memory restoration takes place. It is concluded that the quotions of the other authors ’ texts provide a polyphony of the main text, identify the time series of artistic priorities and the level of the culture of characters. The author relies on the readers’ erudition and artistic preferences, presenting the images offamous heroes of literature, cinema, and pop culture. Much attention is given to intertext, an important tool to demonstrate the problem of suppression of the Ukrainian national struggle and to identify the anti-human essence of the communist ideology. In this novel, the intertext helps to express acute details, feelings and emotions, which dispel the Soviet myth, activating and explaining the problems of the contemporary Ukrainian society.
Literature, cinema and songs in the intertext of Serhii Oksenyk’s novel "The murder of drunk pioneer": the codification of retro-time
Keywords: інтертекст; ретророман; алюзія; цитування; цитації; стилізація; intertext; retro-novel; quotes; quotation; allusions; stylization